A A systematic review of automatic route generation systems - Iparraguirre Leyva, Gian Paul (2025)
Automatic route generation is an essential tool for optimizing logistics, as it reduces operating costs and improves sustainability in a variety of scenarios. This work presents a systematic literature review based on the Kitchenham methodology, which is structured in three phases: planning, execution and reporting, through the analysis of relevant articles obtained from databases such as Scopus and ScienceDirect, 50 relevant studies were identified after the screening stages, Advanced techniques, models, and technologies were obtained that address the main challenges of logistics planning, including adaptation to dynamic environments and real-time decisionmaking. The findings highlight the positive impact of hybrid algorithms and emerging technologies such as the Internet of Things and vehicle connectivity, significantly improving operational efficiency and sustainability. However, challenges persist in their Implementation in areas with limited infrastructure, underscoring the need for more accessible and adaptive solutions for diverse contexts.